Ծիսապաշտամունքային մոտիվները փեսայի շեմին կատարվող հարսանեկան ծիսերգերում - Նվարդ Վարդանյան (ՀՀ ԳԱԱ հրատ.)
Особое внимание уделено мотивам, в которых новобрачные характеризуются как восходящее солнце, в основе которых лежат древние представления о поклонения солнцу, а также восприятие новобрачных как саженецев, связанное с идеей нового роста свадебного дерева. The article investigates the ritual–religious motives of Armenian wedding songs sung at the groom’s threshold. Particular attention is paid to the motives, in which the couple were described as the rising sun, is based on ancient ideas of sun worship. It also investigates the perception of the Bridal sapling associated with the idea of a new growth of the wedding tree.
Keywords: Geography; Ethnography; Manners and customs